UPAYA PENINGKATAN SELF CARE MANAGEMENT MELALUI PENDEKATAN PEER GROUP SUPPORT PADA PASIEN DIABETES MELLITUS - Fakhriatul Falah Fakhriatul; Syamsidar Syamsidar; Mira Astri Koniyo Mira (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
One of the efforts to improve self care management in Patients with Diabetes Mellitus is to provide social support that can provide long-term support in Patients with Diabetes Mellitus. This social support can be provided in the form of peer group support. Objectives: This research aims to improve the self-care management abilities of diabetic mellitus patients and families in the community order. This research is a qualitative study with a grounded theory approach involving 10 people with diabetes mellitus. Data collection uses interview, observation and focus group discussion methods. Results: From the results of thematic analysis, four research themes were found, namely the benefits obtained from participating in peer group, changes in self care, barriers and motivation to join peer group . Conclusions: The application of peer group can increase the motivation of self care management of patients with diabetes mellitus. This study can be applied as one form of health care puskesmas by involving families and people with diabetes mellitus. Keywords: peer group, self care, grounded theory, motivation